THE INFLUENCE OF EMOTIONAL FACTORS, MATERIALISM, RISK PERCEPTION, AND FINANCIAL LITERACY ON THE TENDENCY OF DEBT OF MILLENNIAL GENERATION IN SURABAYA - Richard Widjaja; Dewi Pertiwi (Finance and Investment Program, School of Business and Management - Petra Christian University, 2020)
This study aims to determine the effect of emotion, materialism, risk perception, and financial literacy on the propensity toward indebtedness of the millennial generation in Surabaya. The researcher uses a online questionnaire distributed via Google Form to 110 millennials in Surabaya. The collected data is processed using Partial Least Square (PLS). This study indicates that emotion, materialism, and perceptions have a significant effect on indebtedness propensity.